Effect of tropical forage species in silvopastoral arrangements on methane production and in vitro fermentation parameters in a RUSITEC system - Ibarra-Rondón, Aldo J; Fragoso-Castilla, Pedro J; Giraldo-Valderrama, Luis A; Mojica-Rodríguez, José E (Revista Colombiana de Ciencias Pecuarias, 2022)
Background: Supplementation of grazing cattle with native and naturalized forages using silvopastoral systems has been suggested as an affordable strategy to reduce methane production and improve nutrition, diminishing the environmental impact of cattle production. Objective: To evaluate the effect of three tropical forage species in a silvopastoral arrangement on methane production and fermentation parameters using an in vitro ruminal simulation system (RUSITEC). Methods: Four diets were evaluated. The control treatment was a basal diet of colosuana grass (COL; Bothriochloa pertusa), while the other diets consisted of 70% COL complemented with 30% shrub forage from either Leucaena leucocephala (CL), Guazuma ulmifolia (CG), or Crescentia cujete (CT). A randomized complete block design with repeated measurements over time was used. Results: The inclusion of shrub forage did not affect pH, organic matter degradation (OMD) or volatile fatty acids (VFA). The inclusion of shrub forage affected the degradation of structural components. The concentration of N-NH3 increased in the CL diet compared to COL (p<0.05). In general, methane production in terms of mL/day, mL/g DMi, mL/g DMd, and mL/gOMd was reduced for CL compared to COL (p<0.05). Conclusions: Based on these results, inclusion of Leucaena leucocephala, Guazuma ulmifolia or Crescentia cujete on B. pertusa-based diets improves ruminal fermentation parameters and reduces in vitro methane production.